Effects on Metabolic Health after a 1-Year-Lifestyle Intervention in Overweight and Obese Children: A Randomized Controlled Trial. (19th September 2011) - Waling, Maria; Bäcklund, Catharina; Lind, Torbjörn; Larsson, Christel
Abstract : Objective. To evaluate the effect of a family-based intervention on anthropometric and metabolic markers in overweight and obese children. Methods. Overweight or obese 8–12 years olds ( n = 93) were randomized into intervention or control groups. The intervention group participated in a program aiming for lifestyle changes regarding food habits and physical activity. Anthropometric measures and venous blood samples were collected from all children at baseline and after 1 year. Results. BMI z-scores decreased in both groups, 0.22 (P = 0.002) and 0.23 (P = 0.003) in intervention and control group, respectively, during the 1-year study, but there was no difference in BMI between the groups at 1-year measurement (P = 0.338). After 1 year, there was a significant difference in waist circumference, waist/hip ratio, and apolipoprotein B/A1 ratio between intervention and control group. Conclusions. The intervention had limited effects on anthropometrics and metabolic markers, which emphasizes the need of preventing childhood overweight and obesity.